The Influence of Organizational Culture, Work Environment and Work Motivation on Employee Performance - Lonaldi Lonaldi (Journal on Education, 2023)
This research aims to analyze whether there is an influence between organizational culture, work environment, and work motivation on employee performance. By adopting a quantitative approach and using a cross-sectional design, this research applies a proportional random sampling method, with 100 employees as respondents. Researchers carry out the data collection process through various techniques, such as interviews, questionnaires, observation, and document review. This research conducted data analysis using quantitative descriptive methods and further performed statistical analysis using SPSS software, applying the multiple linear regression method. The research results show that simultaneously, organizational culture, work environment, and work motivation have an influence on employee performance. However, when analyzed partially, organizational culture does not have a significant influence on employee performance. Likewise with the work environment, which also does not have a partially significant influence on employee performance. However, work motivation has been proven to significantly influence employee performance. These findings highlight the importance of motivational factors in improving individual performance in the work environment. Therefore, this research provides valuable insights for companies to develop more effective strategies and policies to improve employee performance.